FHODs: Nuclear tethered formins for nuclear mechanotransduction - Antoku, Susumu; Schwartz, Thomas U.; Gundersen, Gregg G. (Frontiers in Cell and Developmental Biology, 2023)
In this review, we discuss FHOD formins with a focus on recent studies that reveal a new roll for them as critical links for nuclear mechanotransduction. The FHOD family in vertebrates comprises two structurally related proteins, FHOD1 and FHOD3. Their similar biochemical properties suggest overlapping and redundant functions. FHOD1 is widely expressed, FHOD3 less so, with highest expression in skeletal (FHOD1) and cardiac (FHOD3) muscle where specific splice isoforms are expressed. Unlike other formins, FHOD formins have strong F-actin bundling activity and relatively weak actin polymerization activity. These activities are regulated by phosphorylation by ROCK and Src kinases; bundling is additionally regulated by ERK1/2 kinases. FHODs are unique among formins in their association with the nuclear envelope through direct, high affinity binding to the outer nuclear membrane proteins nesprin-1G and nesprin-2G. Recent crystallographic structures reveal an interaction between a conserved motif in one of the spectrin repeats (SRs) of nesprin-1G/2G and a site adjacent to the regulatory domain in the amino terminus of FHODs. Nesprins are components of the LINC (linker of nucleoskeleton and cytoskeleton) complex that spans both nuclear membranes and mediates bidirectional transmission of mechanical forces between the nucleus and the cytoskeleton. FHODs interact near the actin-binding calponin homology (CH) domains of nesprin-1G/2G enabling a branched connection to actin filaments that presumably strengthens the interaction. At the cellular level, the tethering of FHODs to the outer nuclear membrane mechanically couples perinuclear actin arrays to the nucleus to move and position it in fibroblasts, cardiomyocytes, and potentially other cells. FHODs also function in adhesion maturation during cell migration and in the generation of sarcomeres, activities distant from the nucleus but that are still influenced by it. Human genetic studies have identified multiple FHOD3 variants linked to dilated and hypertrophic cardiomyopathies, with many mutations mapping to “hot spots” in FHOD3 domains. We discuss how FHOD1/3’s role in reinforcing the LINC complex and connecting to perinuclear actin contributes to functions of mechanically active tissues such as striated muscle.